A case study on a sustainable alternative to the landfill disposal of spent foundry sand. (1st January 2013) - Nabhani, Farhad; McKie, Martin; Hodgson, Simon
Many small to medium enterprises (SMEs) in the UK are being forced to change the way they manage and dispose of waste. In part, this change has been due to the introduction of landfill taxes by the government, implemented to encourage companies to look at suitable and sustainable alternatives. This case study examines the application of key performance indicators (KPI) to monitor SMEs spent foundry sand (SFS) disposal over a one year period. Monitoring the KPI initiated a company investigation to reduce SFS disposal to landfill and promote its beneficial reuse. Several alternative methods for SFS reuse were examined and a successful partnership was established with an asphalt producer after it was established that SFS could be substituted for virgin sand in asphalt manufacture. In addition to providing cost savings, for both partners, the partnership enabled SFS to be beneficially reused with a potential extension of its useful working life to about 60 years.